Perceived added value of a decision support App for formal caregivers in community‐based dementia care - Thoma‐Lürken, Theresa (J Clin Nurs, 2018)
AIMS AND OBJECTIVES: To gain insight into the perceived added value of a decision support App for district nurses and case managers intended to support a problem assessment and the provision of advices on possible solutions to facilitate ageing in place of people with dementia, and to investigate how they would implement the App in daily practice. BACKGROUND: District nurses and case managers play an important role in facilitating ageing in place of people with dementia (PwD). Detecting practical problems preventing PwD from living at home and advising on possible solutions is complex and challenging tasks for nurses and case managers. To support them with these tasks, a decision support App was developed. METHODS: A qualitative study using semi‐structured interviews was conducted. A photo‐elicitation method and an interview guide were used to structure the interviews. The data were analysed according to the principles of content analysis. RESULTS: In five interviews with seven district nurses and case managers, the added value was described in terms of five themes: (a) providing a broader/better overview of possible solutions; (b) providing a guideline/checklist for problem assessment and advice on solutions; (c) supporting an in‐depth problem assessment; (d) being a support tool for unexperienced case managers/district nurses; and (e) providing up‐to‐date information. The participants regarded the App as complementary to their current work procedure, which they would use in a flexible manner at different stages in the care continuum. CONCLUSIONS: The participants valued both parts, the problem assessment and the overview of possible solutions. An important requisite for the usage would be that the content is continuously updated. Before implementation of the App can be recommended, an evaluation of its effectiveness regarding decision‐making should be conducted. RELEVANCE TO CLINICAL PRACTICE: This study underpins the need of nurses and case managers for decision support with regard to problem assessment and providing advices on possible solutions to facilitate ageing in place of PwD. There results also show the importance of listening to users experience and their perceived added value of decision support tools as this helps to explain the lack of statistically significant effects on quantitative outcome measure in contrast to a high willingness to use the App in a previous study.